Fungsi Komunikasi Pembangunan Dalam Meningkatkan Wisata di Kampung Lama - Irma Yusriani Simamora; Alya Hamzah Panggabean; Riska Amanda Pratiwi; Daffa Yusriyah Daulay; Yughni Faidah (Institut Nalanda, 2024)
In this study, we examined about a tourism that is famous for its culture. Introduction to culture and history that is the main destination on this tour, namely the old comrades located in the old village, Labu Beach. Culture is a legacy from ancestors that must continue to be developed, but because of the many factors that make culture farther from civilization, making the next generation forget and even do not know the existing heritage. Technology is one way to know a culture that has long been lost and even forgotten. In addition, kawan lama tourism is a way to introduce the culture in the old kampung village, the culture is in the form of Malay customs, both dances, typical foods, traditional clothes and traditional Malay tools.